2020
DOI: 10.1096/fj.202000823r
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles: where the amyloid precursor protein carboxyl‐terminal fragments accumulate and amyloid‐β oligomerizes

Abstract: Pleiotropic roles are proposed for brain extracellular vesicles (EVs) in the development of Alzheimer's disease (AD). Our previous studies have suggested a beneficial role for EVs in AD, where the endosomal system in vulnerable neurons is compromised, contributing to the removal of accumulated material from neurons. However, the involvement of EVs in propagating AD amyloidosis throughout the brain has been considered because the amyloid‐β precursor protein (APP), APP metabolites, and key APP cleaving enzymes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 79 publications
(150 reference statements)
0
39
0
Order By: Relevance
“…However, detection of APP and its secretases in exosomes raise the possibility that extracellular vesicles, as reported in earlier studies (Perez-Gonzalez et al, 2020), may also serve as a potential site for de novo APP metabolism. Consistent with our results, Aβ 1-42 treatment which is known to increase cholesterol accumulation within cells (Mohamed et al, 2012) has been shown to decrease exosome secretion from astrocytes in a JNK-dependent pathway (Abdullah et al, 2016).…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 72%
“…However, detection of APP and its secretases in exosomes raise the possibility that extracellular vesicles, as reported in earlier studies (Perez-Gonzalez et al, 2020), may also serve as a potential site for de novo APP metabolism. Consistent with our results, Aβ 1-42 treatment which is known to increase cholesterol accumulation within cells (Mohamed et al, 2012) has been shown to decrease exosome secretion from astrocytes in a JNK-dependent pathway (Abdullah et al, 2016).…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 72%
“…Since the publication of the first protocol for isolation of BDEVs [ 76 ], the number of publications on this topic is increasing, with the first group of those publications reviewed in reference [ 98 ]. Since then, regarding neurodegenerative diseases such as AD, it has been shown that during the preclinical stage the expression of MHC class I markers in BDEVs is significantly upregulated [ 99 ] and that EVs isolated from murine brain are enriched with C-terminal fragments of APP (APP-CTFs), actively produced on the vesicles [ 76 , 100 ]. Furthermore, brain-derived EVs isolated both from early AD subjects and BCAS (bilateral common carotid stenosis) mice carry proteins involved in hypoxia such as EFEMP1, downstream activator of HIFs [ 101 ], highlighting the role of EVs in the hypoperfusion in human dementias.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Upregulation of intraluminal vesicles (ILVs) in MVBs was reported in the Ts2Cje model of DS (D’Acunzo et al, 2019 ). It is noteworthy that exosomes contain APP-derived metabolites raising the possibility of a protective role in removing toxic products, including the C-terminal fragment of 99 amino acids (β-CTFs) and Aβ species (Perez-Gonzalez et al, 2020 ). If exosomes play this role, they may enhance Aβ clearance through a microglial cell-dependent pathway.…”
Section: Mechanisms Of Alzheimer’s Disease In Down Syndromementioning
confidence: 99%